Efimov Trimer Formation via Ultracold Four-Body Recombination - Wang, Yujun; Esry, B. D. (My University, 2009)
We discuss the collisional formation of Efimov trimers via ultracold four-body recombination. In particular, we consider the reaction A+A+A+B→A3+B with A and B ultracold atoms. We obtain expressions for the four-body recombination rate up to an overall constant and show that it reflects the three-body Efimov physics either as a function of collision energy or as a function of the two-body s-wave scattering length between A atoms. In addition, we briefly discuss issues important for experimentally observing this interesting and unexplored process.